The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1364/oe.24.006680
|View full text |Cite
|
Sign up to set email alerts
|

Ideal, constant-loss nanophotonic mode converter using a Lagrangian approach

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…There have been numerous approaches to optimize the design of adiabatic mode-evolution-based devices in integrated optics. For adiabatic tapers, one approach is based on the equalization of taper loss along each propagation step [16][17][18]. A similar approach is to limit the fraction of power scattered into the unwanted mode below a constant value [19].…”
mentioning
confidence: 99%
“…There have been numerous approaches to optimize the design of adiabatic mode-evolution-based devices in integrated optics. For adiabatic tapers, one approach is based on the equalization of taper loss along each propagation step [16][17][18]. A similar approach is to limit the fraction of power scattered into the unwanted mode below a constant value [19].…”
mentioning
confidence: 99%
“…A general design approach has been proposed by Horth et al and a constant-loss framework taper was presented. [8] Firstly, it was theoretically demonstrated that an inverted taper with constant loss as a function of position along the taper would be most efficient. Then, like multistage tapers, Horth divided the taper into small steps and designed every step with the same propagation loss.…”
Section: Introductionmentioning
confidence: 99%
“…The basic design principle of inverted tapers is to calculate a taper profile which can keep a constant loss at any point of the taper. [8] Essentially, the spot-size conversion loss is mainly from effective mode area (EMA) changing along the taper, which means that the rapid EMA changing results in a large spot-size conversion loss. Motivated by this idea, an equation between EMA and the position within the taper, which make the constant-loss condition satisfied, is firstly derived.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations